Delineation of leachate plume migration by electrical resistivity methods Ile Epo dumpsite, Lagos, Southwestern Nigeria - Okpogo, Emele Uduma; Wilkie, Petra Ebisan (Iraqi Journal of Science, 2018)
A 5-traverse 2D resistivity survey and 20 Vertical Electrical Sounding (VES) points were carried out on Ile Epo Dump Site with a view to inferring the extent of migration of leachate plumes in the subsurface for possible contamination of groundwater. The surveys were carried out with Omega model resistivity meter. The Schlumberger configuration was employed for the VES while Wenner configuration was employed for the 2D resistivity survey (Constant Separation Techniques). The obtained VES and CST data were interpreted using WinResist and DIPRO respectively. The integrated results revealed three to four geo-electrically polluted materials as highly saturated fills (15 Ωm, 1.9 – 27.4m), saturated fills (15 - 30 Ωm, 3.6 – 29.9m) and unsaturated fills (30 - 70 Ωm, 8.1 – 37.1m) underlain by sand formation. A good correlation was established between the thickness of the different fills delineated from the VES and CST results to a depth of 30m. Based on the integrated geophysical investigation, it is therefore concluded that aquifer units within and underlying the sand layer around Ile Epo Dumpsite and environs are potentially polluted. However, for groundwater exploration, aquifers at deeper depth are likely to be free from contamination but required time to time monitoring because the underlying sand layer serves as possible migration path to the pollutants, thereby contaminating aquifers within underlying sand layer.